Coberturas mortas de inverno e controle químico sobre plantas daninhas na cultura do milho - Martins, Dagoberto [UNESP]; Gonçalves, Clebson Gomes [UNESP]; Da Silva, Antonio Carlos [UNESP] (My University, 2016)
The correct choice of cover crops improves the sustainability of a farming system, as it can enhance the use of herbicides, reduce weed infestation and improve crop performance. With the aim of studying the effect of winter mulches and the use of herbicides on a community of weeds in maize, a study was carried out in a completely randomised design where the treatments were arranged in a scheme of split lots with four replications. The lots, six in number, comprised the following winter crops: Lupinus albus, sativos Lathyrus, Triticum aestivum, Avena strigosa, Raphanus sativus, and a control kept fallow. The three sub-lots comprised, 1 - spraying the management herbicide before sowing the maize, 2 - management herbicide after sowing the maize + residual herbicide, and 3 - control without the application of herbicide. Mulches of black oat and forage turnip gave the lowest weed densities and accumulations of dry weight in the weed community, irrespective of the application of herbicide. There was greater germination of B. pilosa in the lots maintained with a cover of lupins, with the exception of those sub-lots where herbicide was applied pre-emergence, demonstrating the stimulating effect of mulch. The use of certain species in the formation of mulch under direct planting can dispense with or reduce the amount of herbicides needed for weed control.
Winter mulches and chemical control on weeds in maize
Keywords: Alternate cropping; Herbicide; No-tillage; Plant residue; Zea mays L